(untitled) (Technological Innovations Journal, 2026)
Public infrastructure projects require rigorous estimates of unforeseen costs and time to ensure their technical, contractual, and financial viability. The objective of this study was to estimate the adjusted real value of contingency and management reserves in cost and schedule for road works contracted during 2023 in a Colombian Governor’s Office, considering uncertainty, risk events, and project-related correlations. A quantitative, non-experimental, cross-sectional research was conducted, based on documentary analysis of a representative road construction contract, surveys applied to contractors and experts, review of unit prices and performance, and Monte Carlo simulation using @Risk and SPSS. The analysis identified the contractor’s actual exposure to known and unknown risks, as well as the insufficiency of the percentages currently recognized by the entity. The results show that 71.1% of contractors are unaware of unforeseen events that may affect execution, and 73.9% consider the percentage assigned by the Governor’s Office insufficient. The simulation estimated a total reserve of 3.42% in cost and 3.47% in time, values higher than those applied in practice. It is concluded that the entity underestimates risks in its budgets and schedules, affecting the economic equation of the contract. It is recommended to adopt a technical model based on probabilistic analysis for the estimation of unforeseen events in future infrastructure projects.